Epidemiological profile and visual outcome of ocular trauma in a referral center in northeastern Brazil - Costa,Elaine de Paula Fiod (2019)
Abstract Objectives: To evaluate the epidemiological profile and prognosis of patients with mechanical ocular trauma. Methods: Descriptive cross-sectional observational study of consecutive patients evaluated during a one-year period at a public referral center in São Luis, Maranhão, Brazil. The Ocular Trauma Score (OTS) was used to estimate final visual acuity. The variables were analyzed using the chi-square test with a significance level of 5%. Results: Out of a total of 154 patients (mean age of 30.1 years), 27.92% were younger than 16 years, and 81.8% were men, with most coming from the state's countryside (55.2%). Most of the patients were dependents (34%) or rural workers (19%). Regarding the OTS prognosis, 33.77% of the patients were category 5 and 31.16% category 1 or 2, indicating worse prognosis. The best prognoses (visual outcomes) were inversely proportional to age and time to treatment (p<0.001). Conclusion: Ocular trauma remains an important cause of ocular morbidity in childhood and in informal work. Adult supervision and socio-educational measures are mandatory to change this scenario.